IMPLIKASI KEWAJIBAN NOTARIS DALAM PELAPORAN TINDAK PIDANA PENCUCIAN UANG TERHADAP PRINSIP KERAHASIAAN JABATAN NOTARIS - Vionita, Maria; Tinambunan, Regina Irene; Astrinitha, Mega (Tanjungpura Acta Borneo Journal, 2025)
Abstract Notaries hold a strategic role within the Indonesian legal system, not only as public officials authorized to produce authentic deeds but also as responsible parties in the prevention of money laundering crimes (TPPU). However, the obligation to report suspicious financial transactions, as stipulated in various regulations such as Law Number 8 of 2010 and its derivative provisions, often conflicts with the principle of professional confidentiality that underpins notarial ethics. This study aims to analyze the legal implications of the notary's reporting obligations in the context of money laundering and how this affects the principle of professional confidentiality. Using a normative legal research method with a conceptual approach and literature study, this research shows that although regulations mandate notaries to report suspicious transactions, there are still several implementation challenges, including regulatory inconsistencies, limited understanding, and ethical dilemmas. In addition, suboptimal reporting systems and lack of training also weaken the effectiveness of the notary’s role.This study recommends the need for regulatory strengthening, continuous training and education, the development of efficient reporting systems, strict enforcement of professional ethics, and enhanced inter-institutional collaboration. With a more integrative and systemic approach, the role of notaries as front-line actors in preventing money laundering can be optimized without disregarding the confidentiality principle that forms the foundation of notarial professionalism. Abstrak Notaris memiliki peran strategis dalam sistem hukum Indonesia, tidak hanya sebagai pejabat umum pembuat akta autentik, tetapi juga sebagai pihak yang turut bertanggung jawab dalam pencegahan tindak pidana pencucian uang (TPPU). Namun, kewajiban pelaporan transaksi mencurigakan oleh notaris sebagaimana diatur dalam berbagai regulasi, seperti Undang-Undang Nomor 8 Tahun 2010 dan peraturan turunan lainnya, sering kali berbenturan dengan prinsip kerahasiaan jabatan yang menjadi dasar etika profesi kenotariatan. Penelitian ini bertujuan untuk menganalisis implikasi hukum terhadap kewajiban pelaporan notaris dalam konteks TPPU dan bagaimana hal tersebut mempengaruhi prinsip kerahasiaan profesi. Menggunakan metode penelitian normatif dengan pendekatan konseptual dan studi kepustakaan, penelitian ini menunjukkan bahwa meskipun regulasi telah mewajibkan notaris untuk melaporkan transaksi mencurigakan, masih terdapat kendala implementasi seperti ketidaksesuaian regulasi, keterbatasan pemahaman, serta dilema etika profesional. Di samping itu, sistem pelaporan yang belum optimal dan minimnya pelatihan juga memperlemah efektivitas peran notaris. Penelitian ini merekomendasikan perlunya penguatan regulasi, peningkatan pelatihan dan edukasi berkelanjutan, pengembangan sistem pelaporan yang efisien, penegakan etika profesi, serta penguatan kolaborasi antar lembaga. Dengan pendekatan yang lebih integratif dan sistemik, peran notaris sebagai garda depan dalam pencegahan TPPU dapat lebih optimal, tanpa mengabaikan asas kerahasiaan jabatan yang menjadi pilar profesionalisme kenotariatan.